2015
DOI: 10.3399/bjgp15x685285
|View full text |Cite
|
Sign up to set email alerts
|

A mismatch between population health literacy and the complexity of health information: an observational study

Abstract: BackgroundLow health literacy is associated with poorer health and higher mortality. Complex health materials are a barrier to health. AimTo assess the literacy and numeracy skills required to understand and use commonly used English health information materials, and to describe population skills in relation to these. Design and settingAn English observational study comparing health materials with national working-age population skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
174
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(188 citation statements)
references
References 9 publications
4
174
0
2
Order By: Relevance
“…Just as the readability of health information needs to match the literacy skills of its users (Rowlands, et al, 2015), so does the readability of health information and services online. In England, around 11 million people lack basic digital literacy, with around 7 million having never used the internet (ONS, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Just as the readability of health information needs to match the literacy skills of its users (Rowlands, et al, 2015), so does the readability of health information and services online. In England, around 11 million people lack basic digital literacy, with around 7 million having never used the internet (ONS, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…All detract from patients' capacities to comply with ED follow-up instructions. Health materials are written at levels of complexity that poorly match population health literacy levels, with approximately half of all sampled printed materials generated in health care settings written at a level of complexity beyond the skills of the patients for whom they were intended [13]. A recent systematic review found that at least 40% of ED patients possess health literacy at or below the eighth-grade level.…”
Section: Introductionmentioning
confidence: 97%
“…Low health literacy affects a significant proportion of English adults; 6 in 10 (61%) adults aged between 16 and 65 years of age in England lack the literacy and numeracy skills to fully understand common health-related information [2]. …”
Section: Introductionmentioning
confidence: 99%